Sodium glucose‐linked transport protein 2 inhibitors: An overview of genitourinary and perioperative implications. (22nd June 2021) - Chandrashekar, Mohit; Philip, Stuart; Nesbitt, Alexander; Joshi, Andre; Perera, Marlon
Abstract: Sodium glucose‐linked transport protein 2 inhibitors are relatively novel drugs, used for the treatment of type 2 diabetes mellitus. Their use since Pharmaceutical Benefits Scheme approval in Australia has increased drastically, possibly due to the low risk of hypoglycemic events and their advertised cardiovascular mortality benefits. However, as with any novel drug, adverse effects regarding their use require medical practitioner awareness for optimal patient outcomes. This paper aims to cover the major urological implications, including those pertinent perioperatively, that concern this class of drugs. There is a clear risk of developing genital mycotic infections with the use of sodium glucose‐linked transport protein 2 inhibitors, including serious infections such as Fournier's gangrene. Evidence for developing urinary tract infections has been mixed. Sodium glucose‐linked transport protein 2 inhibitor‐induced lower urinary tract symptoms may have impacts on quality of life via pollakiuria and nocturia, of which there are increased reports. Perioperative use increases the risk of euglycemic diabetic ketoacidosis. It is recommended that sodium glucose‐linked transport protein 2 inhibitors be ceased perioperatively.